SHARIA FINTECH PROSPECTS (P2P LENDING) ON MSME FINANCING IN INDONESIA - Hartutik Hartutik; R Melda Maesarach; Jaharuddin Jaharuddin (Jurnal Ilmiah Ekonomi Islam, 2023)
This study aims to determine the business prospects of Sharia Fintech Lending in Indonesia. In practice, this research uses quantitative methods with trend analysis. The results of the study show that Islamic Fintech Lending has large and wide financing opportunities in Indonesia. This is evident from the results of research showing that the average increase in Islamic Fintech Lending financing is 45%, very high compared to the average increase in conventional bank financing of 0.68%, Islamic Bank 0.42%, Conventional Fintech Lending 11%. This means that even though Sharia Fintech Lending is in the beginner category, it has been able to attract public interest, besides the number of Indonesians who are predominantly Muslim, it is an opportunity for the development of Sharia Fintech Lending. The results of this study are expected to be able to provide a reference for policy makers and Sharia fintech business players, to be able to improve the performance of Sharia fintech lending in Indonesia. Key Word : P2P, Fintech Lending Sharia, Financing, MSME